CD36 gene polymorphism rs1761667 (G > A) is associated with hypertension and coronary artery disease in an Iranian population - Mohammad Amin Momeni-Moghaddam; Gholamreza Asadikaram; Hamed Akbari; Moslem Abolhassani; Mohammad Masoumi; Zahra Nadimy; Mohammad Khaksari (BMC Cardiovascular Disorders, 2019)
Abstract Background CD36 is associated with regulation of lipid metabolism, atherosclerosis, and blood pressure. Moreover, its variation may be involved in the development of hypertension and/or coronary artery disease (CAD). The present study was conducted to investigate the possible association of CD36 rs1761667 (G > A) polymorphism with hypertension and/or CAD in the southeastern of Iran. Methods The present observational study was composed of 238 subjects who were admitted for coronary angiography, and divided into four groups: 1) hypertensive without CAD (H-Tens, n = 52); 2) hypertensive with CAD (CAD + H-Tens, n = 57); 3) CAD without hypertension (CAD, n = 65); and 4) non-hypertensive without CAD as the control group (Ctrl, n = 64). The CD36 rs1761667 polymorphism was genotyped with PCR-RFLP method. Association between CD36 rs1761667 genotypes and the risk of CAD and hypertension was assessed using multinomial regression by adjusting for age, sex, creatinine, fasting blood sugar (FBS), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Results In the present study, minor allele (A) frequency was 0.36. The genotype, but not allele frequency of the CD36 rs1761667 was significantly different between the four study groups (p = 0.003). Furthermore, using a recessive inheritance model CD36 rs1761667 polymorphism was significantly associated with an increased risk of CAD with hypertension (OR = 5.677; 95% CI = 1.053–30.601; p = 0.043). However, using the dominant model of CD36 rs1761667 had a protective effect on H-Tens and CAD patients. Conclusion The present findings revealed an association between CD36 rs1761667 polymorphism and susceptibility to hypertension and/or CAD in a southeastern Iranian population.